Assessment of Failure and Repair Behaviours of the Jebba Hydroelectric Power Station - Thomas, Cornelius Temitope; Ogunbiyi, Olalekan; Akorede, Mudathir Funsho; Olufeagba, Jimi Benjamin (ELEKTRIKA- Journal of Electrical Engineering, 2018)
Nigeria power generation is circa 4000 MW as at October 2016, this is far less than the national required value. Jebba Hydroelectric Power Station (JHEPS) is one of the three major hydropower stations in the country which its maximum average generation value is still less than the rated value of 578.4 MW. This paper presented some basic concepts of analysis of failure and repair. An algorithm was set up to extract the contiguous set of up-times and down-times to determine time-tofail (TTR) and time-to-repair (TTR) events, these events were analyzed for stochastic study. It was observed that the longest up time was 262 days and seen in turbo-alternator unit five, while the shortest was zero day and seen in the entire units except that of unit two. The longest downtime was 133 days and seen in the turbo-alternator of unit one, the least time-to-repair is a day and common to all the units. The frequency distributions for both TTF and TTR showed that 79% of TTF events and 57% of TTR events are distributed in the first 2 classes